SANKSI PIDANA TERHADAP PELAKU KDRT DARI PERSPEKTIF KEPENTINGAN PEREMPUAN - Emilia Ninik, Aydawati; B. Resti, Nurhayati; Venatius, Hadiyono (Seri Kajian Ilmiah, 2014)
A home is a place where every member gets protection. However, a home sometimes can be a source of suffering due to the acts of domestic violence. The enactment of Law No. 23 of 2004 on Abolition of Domestic V54+-iolence does not automatically lead to the rate decrease of domestic violence because many victims have no courage to bring the case as a legal matter. Actually the Act on Abolition of Domestic Violence provides severe penalties for the perpetrators, but in practice the imposed penalties for the perpetrators are often more lenient than the penalty suggested by the Act. This research is qualitative. The secondary data were taken from legal court verdicts. To complete the data, interviews were conducted to the judges making the verdicts in order to understand the considerations in deciding the penalities about domestic violence cases. The conclusion of this study is the fact that penalties imposed by the judges tend to be lower than the prosecutorâs demand. Besides, the trial process is more dominated by physical violence acts than the other three violences. In making their decision, the judges merely base on the Act on Elimination of Domestic Violence. For the cases involving children as the victims the judges also base their decisions on the Act on Child Protection. Seeing that the view from womenâs interest appears to be a mainstream, the judges have to be extra careful in handling domestic violence cases in order to impose appropriate criminal penalties, that meet the principles of justice, expediency and legal certainty